VARIATION TERMINOLOGIQUE DANS LA TRADUCTION DES DOCUMENTS OFFICIELS RELATIFS À LA COVID-19 - Cristina Ilinca (Studii de gramatică contrastivă, 2021)
The purpose of our article is to analyse the concept of terminological variation in the transmission of information from official institutions to the public in the context of the 2019-2021 health crisis. More precisely, we dealt mainly with press releases and other official texts in English of the European Council and the European Commission translated into Romanian which have been analysed from the point of view of the use of the COVID-19 terminology in order to see there is a unitary or rather heterogeneous use given the rapid and unexpected evolution of the pandemic and the extraordinary communication dynamics that has characterised this period.